Randomized Phase II Trial of Triapine-Cisplatin-Radiotherapy for Locally Advanced Stage Uterine Cervix or Vaginal Cancers - Kunos, Charles A.; Andrews, Stephen J.; Moore, Kathleen N.; Chon, Hye Sook; Ivy, S. Percy (Frontiers in Oncology, 2019)
Uterine cervix or vaginal cancers have inherent overactivity of ribonucleotide reductase (RNR), making these cancers rational targets for therapy based on interruption of cisplatin-radiotherapy-induced DNA damage repair. We conducted a pilot, open-label randomized phase II trial to evaluate the efficacy and safety of cisplatin-radiotherapy with or without triapine, a small molecule with RNR-inhibitory activity, in patients with advanced-stage uterine cervix or vaginal cancers ((NCT01835171), as a lead in to a randomized phase III study (NCT02466971). A total of 26 women were randomly assigned to receive six weeks of daily radiotherapy followed by brachytherapy (80 Gy) and once-weekly cisplatin (40 mg m-2)—with or without three-times weekly intravenous triapine (25 mg m-2)—in one 56-day cycle. Primary end points were metabolic complete response by positron emission tomography and safety. Additional end points included the rate of clinical response, rate of methemoglobinemia, and progression-free survival. The addition of triapine to cisplatin-radiotherapy improved the rate of metabolic complete response from 69% to 92% (P=0.32) and raised the 3-year progression-free survival estimate from 77% to 92% (hazard ratio for progression, 0.30; P=0.27). The most frequent grade 3 or 4 adverse events in either treatment group included reversible leukopenia, neutropenia, fatigue, or electrolyte abnormalities. No significant differences were seen between the two groups in the rate of adverse events. Symptomatic methemoglobinemia was not encountered after triapine infusion. In conclusion, the addition of triapine to cisplatin-radiotherapy improved the rate of metabolic complete response in patients with advanced-stage uterine cervix or vaginal cancers without significant toxicity. A phase III trial adequately powered to evaluate progression-free and overall survival is underway (NCT02466971).